Elastin imaging enables noninvasive staging and treatment monitoring of kidney fibrosis - Qinxue Sun; Maike Baues; Barbara M. Klinkhammer; Josef Ehling; Sonja Djudjaj; Natascha Drude; Christoph Daniel; Kerstin Amann; Rafael Kramann; Hyojin Kim; Julio Sáez-Rodríguez; Ralf Weiskirchen; et al. (2019)
Fibrosis is the common endpoint and currently the best predictor of progression of chronic kidney diseases (CKDs). Despite several drawbacks, biopsies remain the only available means to specifically assess the extent of renal fibrosis. Here, we show that molecular imaging of the extracellular matrix protein elastin allows for noninvasive staging and longitudinal monitoring of renal fibrosis. Elastin was hardly expressed in healthy mouse, rat, and human kidneys, whereas it was highly up-regulated in cortical, medullar, and perivascular regions in progressive CKD. Compared to a clinically relevant control contrast agent, the elastin-specific magnetic resonance imaging agent ESMA specifically detected elastin expression in multiple mouse models of renal fibrosis and also in fibrotic human kidneys. Elastin imaging allowed for repetitive and reproducible assessment of renal fibrosis, and it enabled longitudinal monitoring of therapeutic interventions, accurately capturing anti-fibrotic therapy effects. Last, in a model of reversible renal injury, elastin imaging detected ensuing fibrosis not identifiable via routine assessment of kidney function. Elastin imaging thus has the potential to become a noninvasive, specific imaging method to assess renal fibrosis.